Pendampingan Pengolahan Sistem Informasi Pendataan dokumen Sekolah Berbasis Komputerisasi di SMK Negeri 3 Lhokseumawe - Mutammimul Ula; Cut Ita Erliana; Zahratul Fitri; Fakrurrazi; Angga Pratama (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2022)
The document data collection process is one of the administrative management processes that are still using manually for now. this is for such administrative management takes a long time so it is not effective and efficient. To overcome these problems, efforts are needed to provide knowledge about computer applications. With the existence of an information system for computerized document administration will facilitate the work properly and effectively. The problem raised in this service is how to make computer applications in management information systems administratively and computerized document data collection and can be neatly arranged for all documents. The second problem is how to implement a management information system in a directed manner so that the documents you are looking for are arranged properly. The problem so far is that the management information system data processing mostly uses a manual processing system, still uses a ledger and is stored in a cupboard. The system, of course, has many weaknesses and in terms of administration, poor presentation, sub-optimal service, and low data quality. The purpose of this service is to help manage data and finances to be more effective and efficient. So that the information from the data entered can be conveyed properly. The result of this service is an explanation of how the Computerized Document Data Collection Administration Management Information System with various features can be used to manage student, teacher, staff data in managing all files.